Entrepreneurial management in small firms - Chaston, Ian.; Ian Chaston (London : SAGE, 2010)
Written by a leading light on the topic, this text examines the processes by which small businesses identify new opportunities, evolve appropriate marketing strategies, develop new products and services and launch these into the market.
Includes bibliographical references and index.
eng.
Keywords: Small business; Entrepreneurship; Small business